PRODUKSI, SEKUESTRASI DAN SEBARAN KARBON KANGKUNG AIR (Ipomoea aquatica, Forsk. L.) PADA KEBUN TELAGA DI DESA KALASEY SATU - Syamsiar A. R.; Joko Purbopuspito; Jenny J. Rondonuwu (COCOS, 2017)
ABSTRACT  Biomass production of water spinach is a photosynthetic carbon assimilation by Ipomoea aquatica, Forsk. L. in reducing carbon in the air.  Water spinach grown at cultivated ponds of Kalasey Satu village followed natural irrigation system. We determined this water spinach biomass production and its carbon sequestration.  Soils and leafy vegetable products were sampled from upstream (Block A) to downstream (Block C) in 4 replicates per block for 3 consecutive observations.  Soil bulk densities in Block A (0.33 g.cm-3) is significantly heavier that that in Block C (0.22 g.cm-3) and soil depth in Block C (96 cm) was significantly deeper than solum depth in Block B (61 cm). Carbon production in water spinach, however, were not significantly different among blocks during 3 observation times.  Carbon sequestration of 20 days interval is 1.21 kg C.ha-1 which is equivalent to 22.1 kg C.ha-1.y-1.  Farmers' income from carbon sequestration is about Rp 551.958,- ha-1.y-1 and equivalent to USD 42.46 ha-1.y-1.  Keywords:  Water spinach (Ipomoea aquatica, Forsk. L.), vegetable production, carbon sequestration and carbon stock distribution